What’s the point of tobacco control? Comment on Dan Halliday, ‘The ethics of a smoking licence’ - Voigt, K (BMJ, 2016)
Sales taxes have become a central feature of anti-smoking initiatives across the world. Dan Halliday provides a strong argument in favour of smoking licences as an alternative to suchtaxes.[1] I agree with much of Dan’s argument. For this commentary, I want to take a cue fromDan’s points about the relationship between ideal and non-ideal theory. In particular, I want to take a step back to consider on what basis we should assess the relative merits of different antismoking interventions such as taxes and licenses and, more broadly, what the goal of tobacco control and anti-smoking initiatives should be. While this may at first glance seem obvious – the goal, one might argue, is to reduce smoking as much as possible and, ideally, to eradicate it entirely – such a response would, I think, be too quick. Much is to be gained from considering in more detail what the goals of tobacco would be if we could abstract from, or ‘assume away’, certain aspects of the real world, before considering how these goals might need to be adapted in light of real-world constraints.